Cisti Parapieliche. Un Elemento di Sospetto Per la Diagnosi di Malattia di Fabry - Livia Maria Sorrentino; Luigi Annicchiarico Petruzzelli; Angela Maria Pellegrino; Cristina Marchetiello; Maria Amicone; Eleonora Riccio; Antonio Pisani (AboutScience Srl, 2017)
Abstract non disponibile